2022
DOI: 10.24235/eltecho.v7i1.9905
|View full text |Cite
|
Sign up to set email alerts
|

Digital Teaching Awareness and Practice: Narratives From Indonesian Esp Teachers

Abstract: Research on the integration of digital technology in English language teaching has enormously been conducted. However, studies exploring digital teaching awareness and practice among English for specific purposes (ESP) teachers still remain a paucity of evidence. The present study aims to examine Indonesian ESP teachers" digital teaching awareness and technology-based classroom activities. To reach the objective, qualitative approach under the procedure of narrative inquiry is applied. Semi-structured intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Therefore, simply being aware is insufficient for teachers to claim that they are digitally literate and ready for technologically integrated transformation, as digital literacy covers a broad spectrum that discusses teachers' ability to utilise technology effectively. Further, the studies of Nugroho et al and Mutiaraningrum and Nugroho [85,88] also confirmed the need for meaningful awareness that can extend up to effective use of technology, creating innovative learning environments [85,88]. According to Tam [89], an accidental shift in teachers' behaviours is observed in response to alterations in the educational environment.…”
Section: Teachers' Awareness Of Technologymentioning
confidence: 82%
See 2 more Smart Citations
“…Therefore, simply being aware is insufficient for teachers to claim that they are digitally literate and ready for technologically integrated transformation, as digital literacy covers a broad spectrum that discusses teachers' ability to utilise technology effectively. Further, the studies of Nugroho et al and Mutiaraningrum and Nugroho [85,88] also confirmed the need for meaningful awareness that can extend up to effective use of technology, creating innovative learning environments [85,88]. According to Tam [89], an accidental shift in teachers' behaviours is observed in response to alterations in the educational environment.…”
Section: Teachers' Awareness Of Technologymentioning
confidence: 82%
“…Teachers' understanding of the potential of technology towards education is discussed under digital awareness; accordingly, teachers are required to maintain strong technological awareness [83,84]. Awareness shapes their use of technology [85,86] and helps teachers to improve [54]. Awareness supports in creating teachers' beliefs and beliefs about technology influence how teachers use technology in teaching [87].…”
Section: Teachers' Awareness Of Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…In the realm of collaborative online learning, the integration of technology has become pivotal in optimizing ESP instruction. The use of various technological tools both social networking sites and web-based materials (Nugroho et al, 2022) as well as the support of infrastructure, such as virtual classrooms, multimedia resources with the support of excellent internet connection enhances the delivery of ESP content and provides students with authentic learning experiences. Through online platforms, ESP courses can be designed to simulate real-world scenarios, allowing learners to finally assist the students specifically address the needs of students as they relate to their goals for learning English.…”
Section: Discussionmentioning
confidence: 99%
“…According to (Abbad et al, 2009), the use of digital technology is mandatory in online learning and teaching. Meanwhile, (Nugroho et al, 2022), states that teachers' awareness of technology for educational purposes is highly recommended. Teachers need to adjust their old habits to a new situation (Altan & Lane, 2018).…”
Section: Introductionmentioning
confidence: 99%